RANCANG BANGUN GAME EDUKASI DENGAN MENGGUNAKAN FINITE STATE MACHINE - Khaerudin, Muhamad; Setiadi, Dedi; Sumitra, Tata (Universitas Dirgantara Marsekal Suryadarma, 2022)
Learning media is a tool that can help the teaching and learning process and serves to clarify the meaning of the message conveyed, so that it can achieve learning objectives better and more perfectly. There are several methods or ways to carry out learning activities. One of them is learning activities using interactive media to be given to students. The purpose of interactive educative as a teaching and learning process between teachers and students includes increasing competence in three aspects, namely cognitive, psychomotor, and affective aspects. Offline activities in the classroom or online a teacher is expected to be more creative in making learning creations and innovations as well as to focus learning on students. One of the learning activities using interactive media to be given to students is games. This educational game is Hinterweltlern with the Role Playing Gaming genre by using a game engine, Blender for 3D modeling, , and Finite State Machine for designs that determine behavior, actions, and states. With the results of this game research is to update the curriculum and learning media usedÂ Keywords Â : Learning media, educational game, Finite State Machine, designs